Large-vessel vasculitis - Pugh,D; Karabayas,M; Basu,N; Cid,MC; Goel,R; Goodyear,CS; Grayson,PC; McAdoo,SP; Mason,JC; Owen,C; Weyand,CM; Youngstein,T; et al. (Nature Reviews Disease Primers, 2022)
Large-vessel vasculitis (LVV) manifests as inflammation of the aorta and its major branches and is the most common primary vasculitis in adults. LVV comprises two distinct conditions, giant cell arteritis and Takayasu arteritis, although the phenotypic spectrum of primary LVV is complex. Non-specific symptoms often predominate and so patients with LVV present to a range of health-care providers and settings. Rapid diagnosis, specialist referral and early treatment are key to good patient outcomes. Unfortunately, disease relapse remains common and chronic vascular complications are a source of considerable morbidity. Although accurate monitoring of disease activity is challenging, progress in vascular imaging techniques and the measurement of laboratory biomarkers may facilitate better matching of treatment intensity with disease activity. Further, advances in our understanding of disease pathophysiology have paved the way for novel biologic treatments that target important mediators of disease in both giant cell arteritis and Takayasu arteritis. This work has highlighted the substantial heterogeneity present within LVV and the importance of an individualized therapeutic approach. Future work will focus on understanding the mechanisms of persisting vascular inflammation, which will inform the development of increasingly sophisticated imaging technologies. Together, these will enable better disease prognostication, limit treatment-associated adverse effects, and facilitate targeted development and use of novel therapies.